2013
DOI: 10.1186/1471-2148-13-203
|View full text |Cite
|
Sign up to set email alerts
|

A new xinjiangchelyid turtle from the Middle Jurassic of Xinjiang, China and the evolution of the basipterygoid process in Mesozoic turtles

Abstract: BackgroundMost turtles from the Middle and Late Jurassic of Asia are referred to the newly defined clade Xinjiangchelyidae, a group of mostly shell-based, generalized, small to mid-sized aquatic froms that are widely considered to represent the stem lineage of Cryptodira. Xinjiangchelyids provide us with great insights into the plesiomorphic anatomy of crown-cryptodires, the most diverse group of living turtles, and they are particularly relevant for understanding the origin and early divergence of the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(180 citation statements)
references
References 64 publications
5
174
1
Order By: Relevance
“…The anterior suture with the palatines is preserved and broadly convex. The sella turcica is broad and forms an overhang that covers the enlarged and widely spaced foramina anterior canalis carotici cerebralis (sensu Rabi et al 2013). The clinoid processes and the rostrum are damaged, and therefore, their morphology cannot be assessed.…”
Section: Descriptionmentioning
confidence: 99%
“…The anterior suture with the palatines is preserved and broadly convex. The sella turcica is broad and forms an overhang that covers the enlarged and widely spaced foramina anterior canalis carotici cerebralis (sensu Rabi et al 2013). The clinoid processes and the rostrum are damaged, and therefore, their morphology cannot be assessed.…”
Section: Descriptionmentioning
confidence: 99%
“…The internal carotid artery enters the skull halfway along the contact between the pterygoid and basisphenoid, but splits immediately within the skull into the palatine and cerebral branches (Gaffney 1975). It is therefore a question of semantics whether a true foramen posterius canalis carotici interni is present or, rather, tightly spaced foramina posterius canalis carotici palatinum and cerebralis (sensu Rabi et al 2013). The quadrates form a large cavum tympani and low mandibular condyles.…”
Section: Craniummentioning
confidence: 99%
“…The monophyly of Paracryptodira is currently under debate, as some analyses retrieve them as monophyletic (e.g., Joyce 2007;Anquetin 2012;Gaffney et al 2007;Rabi et al 2013), but others as paraphyletic (e.g., Sterli et al 2013). All analyses agree that baenids diverged very close to the base of crown Testudines, but there is disagreement if they are situated at the base of Pan-Cryptodira (e.g., Joyce 2007), just outside of crown Testudines (e.g., Sterli et al 2013) or in an unresolved polytomy (e.g., Anquetin 2012).…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…Joyce (2007) included an expanded sample by scoring Plesiochelys etalloni, Portlandemys mcdowelli, Jurassichelon oleronensis (his "Thalassemys" moseri), and Solnhofia parsonsi as terminal taxa, but they were found in a paraphyletic arrangement. More recent global phylogenetic analyses of turtles continued to include these species as separate terminal taxa Parham 2006, 2008;Sterli 2010;Anquetin 2012;Rabi et al 2013;Sterli et al 2013;Zhou et al 2014;Zhou and Rabi 2015), but none found them to form a monophyletic group.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…Jurassichelon oleronensis is based on a single specimen (PIMUZ A/III 514) from the Tithonian of the Isle of Oléron, France (Rieppel 1980). This specimen represents one of the few skull-shell associations known for thalassochelydians and is therefore regularly included into phylogenetic analyses (e.g., Gaffney and Meylan 1988;Joyce 2007;Sterli 2010;Anquetin 2012;Rabi et al 2013). Rieppel (1980) originally referred this specimen to Thalassemys moseri Bräm, 1965, but pointed out that this species was probably more closely related to Plesiochelys than to Thalassemys hugii.…”
Section: Jurassichelon Oleronensis Pérez-garcía 2015bmentioning
confidence: 99%